Gliricidia intercropping in maize farming: IPSR Innovation Profile - Thierfelder, Christian L. (CGIAR System Organization, 2022)
The sustainable intensification initiatives of Southern Africa use Gliricidia sepium, a leguminous tree species which is well adapted to the environment for their sustainable intensification practices. The importance of this system is to grow the trees in hedge rows or as dispersed trees so that leaves can be utilized in a “chop and drop” fashion with limited labour needed for transporting the biomass from one plot to the other. The spatial arrangement also aims at keeping the competition as low as possible while reaping the benefits of the agro-forestry species. Maize-Gliricidia hedgerow and Maize-Gliricidia disbursed shading are the two main systems. In the first one, maize legume rotations are planted at normal plant population, in addition, hedgerows of Gliricidia trees are planted in rows spaced 5 m apart with an in-row spacing of 1 m. In the second, the disbursed shading system aims at developing larger Gliricidia trees that provide shade, less competition and in addition some green leaves that can be applied to the soil after pruning every year. One tree is usually planted every 10 m in rows 5 m apart.